Miss Pettigrew lives for a day [compact disc, unabridged] - Watson, Winifred, 1906-2002 (Persephone], 2008)
Miss Pettigrew is a down-on-her-luck, middle-aged governess in London sent by her employment agency to work for nightclub singer Delysia LaFosse, rather than a household of unruly children. Over a period of 24 hours her life is changed forever.